Multi-character population study of the vir subtelomeric multigene superfamily of Plasmodium vivax, a major human malaria parasite - Merino, Emilio F.; Fernandez-Becerra, Carmen; Durham, Alan M; Ferreira, João E.; Tumilasci, Vanessa F.; d’Arc-Neves, Joana; Silva-Nunes, Monicada; Ferreira, Marcelo U.; Wickramarachchi, Thilan; Udagama-Randeniya, Preethi; Handunnetti, Shiroma M.; del Portillo, Hernando A. (Molecular and Biochemical Parasitology, 2006)
Plasmodium vivax, the most widely distributed human malaria parasite, contains the subtelomeric multigene vir superfamily corresponding to circa 10% of its coding genome. In this work, we used a multi-character strategy to study the vir gene repertoire circulating in natural parasite populations obtained directly from 32 human patients from endemic regions of Brazil and Sri Lanka. Cladistic analysis confirmed the existence of vir subfamilies, which varied in size and allele polymorphisms. Moreover, different motifs, protein domain, and secondary structures were predicted for each subfamily. Of importance, not all vir sequences possess a recognizable Pexel motif recently shown to be important, though not essential, signal for transportation to the cell membrane of infected red blood cells. Furthermore, subfamilies A and D display common structural features with the recently described P. falciparum SURFIN and Pfmc-2tm subtelomeric multigene families. These results suggest that VIR proteins can have different subcellular localizations and functions. This is the first study on a population level of the P. vivax vir subtelomeric multigene superfamily.
Keywords: Variant genes; Plasmodium vivax; Malaria; vr subtelomeric multigene family; Multi-character in silico analysis